Hospital Service Quality and Outpatient Satisfaction in Model Hospitals in India. Issue 3 (3rd July 2022) - Patel, Hiren J.; Patel, Nikunjkumar D.
Abstract: The purpose of the study is to understand the effect of hospital service quality dimensions on outpatient satisfaction and to understand which demographic variables impacting outpatient satisfaction. A cross-sectional design with a convenient sample of 316 outpatients was surveyed from 29 model hospitals across 15 states of India. CFA and SEM are used for analysis. The hospitals which are interested in increasing outpatient satisfaction should consider income level and education. The overall result of the study helps the hospitals to frame their overall branding, communication and marketing strategy and focus areas to improve upon for service excellence.